Empirical determinants of Malaysia’s trade relation with Nigeria; - Agboola, Yusuf Hammed; Zainal Abidin, Irwan Shah; Bakar, Normizan (2018)
It has been observed that extant literature has been devoted to the study of China’s trade relationship with various developing countries, especially Africa and Nigeria in particular. However, the economy of Malaysia is fast growing among other Asian countries as it spreads her trade tentacles with very many countries, even Nigeria inclusive has been a member of OIC countries. Notwithstanding this trend, there exists little or no empirical study that has examined empirical determinants of Malaysia’s trade with Nigeria despite evidence of her long-standing relationship with Nigeria. It is these developments that motivated this study. Data were collected on the total export of Malaysia to Nigeria alongside with other variables that are theoretically believed to facilitate trade flows from various sources (UNCTAD, WDI, and CEPII) for the period of 1985-2016. The Gravity model was specified first with the traditional variables and was augmented with other macroeconomic and trade variables that predict bilateral trade flows among different economies. The results showed that economic size and distance between Malaysia and Nigeria were not significant in determining Malaysia’s trade flows to Nigeria. However, in the augmented model, nominal GDP of Nigeria, the distance between the two countries, the real and official exchange rate of Nigeria, and FDI inflows to Malaysia were the positive determinants of Malaysia’s trade with Nigeria. On the other hand, GDP growth rate of Malaysia, per capita GDP of Nigeria, and the real exchange rate of Malaysia negatively determined her trade flow with Nigeria.